Pengaruh Good Corporate Governance dan Enterprise Risk Management Diskclosure terhadap Financial Distress - Zulvanya Anissa Fitri; Taswan (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the effect of good corporate governance and enterprise risk management disclosure on financial distress, when managerial ownership, concentration of ownership, and the board of directors are included in good corporate governance. Using the purposive sampling method, the sample for this research is 162 data from 54 manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Descriptive statistical test, classical assumption test, logistic regression test, model feasibility test, hypothesis test are used as analytical tools. The results of this study indicate that managerial ownership has no significant positive effect on financial distress, ownership concentration has no significant negative effect on financial distress, and the board of directors has a significant positive effect on financial distress and enterprise risk management disclosure has a significant negative effect on financial distress.